The Covid-19 Pandemic and the Rights of the Individual in Terms of Private and Public Law - Харитонов, Євген Олегович; Харитонов, Є. О.; Харитонов, Евгений Олегович; Kharytonov, Yevhen O.; Kharytonov, Evgen; Харитонова, Олена Іванівна; Харитонова, О. І.; Харитонова, Елена Ивановна; Kharytonova, Оlena I.; Колодін, Денис Олексійович; Колодін, Д. О.; Колодин, Денис Алексеевич; et al. (Quito : Los Hemisferios University, 2020)
The principles of adjusting the regulation of civil relations in the context of the Covid-19 pandemic are analyzed. The admissibility of restricting human rights in the context of the conflict of private and public interests are researched. Besides, the authors tried to determine the optimal algorithm of government actions aimed at preventing the spread of the epidemic. The main approach to the understanding of human rights in the article is based on Dworkin's concept of “rights as trumps”. A system of such categories as “a man”, “a private person”, “natural private rights”, “private law” and “national civil law” is analyzed. The conclusion is that the importance of the category of “natural” human rights is underestimated, which exacerbates the problem of ensuring human rights in a pandemic, when the state actively uses public law to cope with the crisis. As a result, there is a conflict of basic principles of private and public law: “everything is allowed except what is prohibited by law” vs. “only what is allowed by law is possible”. It is proposed to assume that the usual way of the legal existence of a person is that he/she acts as a participant in civil relations of a private type, even in a pandemic. Private relations, which arise during the quarantine period, are proposed to be regulated mainly by private law methods, limiting the influence of the state. This will allow us to reach a compromise of private and public interests, without restricting the rights of individuals voluntarily.

Проаналізовано принципи регулювання цивільних відносин в контексті пандемії Covid-19. Досліджується допустимість обмеження прав людини в контексті колізії приватних та державних інтересів. Крім того, автори намагались визначити оптимальний алгоритм дій уряду, спрямованих на запобігання поширенню епідемії. Основний підхід до розуміння прав людини у статті ґрунтується на концепції Дворкіна "права як козирі". Проаналізовано систему таких категорій, як "людина", "приватна особа", "природні приватні права", "приватне право" та "національне цивільне право". Висновок полягає в тому, що значення категорії «природних» прав людини недооцінюється, що загострює проблему забезпечення прав людини в умовах пандемії, коли держава активно використовує публічне право для подолання кризи. В результаті виникає колізія основних принципів приватного та публічного права: «дозволено все, за винятком того, що заборонено законом», та «можливо лише те, що дозволено законом». Запропоновано припустити, що звичайним способом легального існування особи є те, що вона виступає як учасник цивільних відносин приватного типу, навіть в умовах пандемії. Приватні відносини, що виникають під час карантину, пропонується регулювати переважно приватноправовими методами, обмежуючи вплив держави. Це дозволить нам досягти компромісу між приватними та державними інтересами, не обмежуючи добровільно права людей.
Kharytonov E. The Covid-19 Pandemic and the Rights of the Individual in Terms of Private and Public Law / E. Kharytonov, O. Kharytonova, D. Kolodin, M. Tkalych // Ius Humani. Law Journal. – V. 9 (2). – Quito : Los Hemisferios University, 2020. – P. 225-250.
Keywords: human rights; private person; private law; public law; pandemic Covid-19; права людини; приватна особа; приватне право; публічне право; пандемія Covid-19; права человека; частное лицо; частное право; публичное право; пандемия Covid-19; Research Subject Categories::LAW/JURISPRUDENCE